Hybrid Rigid/Soft and Biologic/Synthetic Materials: Polymers Grafted onto Cellulose Microcrystals - Harrisson, Simon; Drisko, Glenna L.; Malmstrom, Eva; Hult, Anders; Wooley, Karen L. (Biomacromolecules, 2011)
Rigid nanoscale polymer rods were prepared by grafting preformed amine-terminated poly(styrene) and poly(tert-butyl acrylate) onto oxidized cellulose microcrystals. Low polydispersity polymers, grown using atom transfer radical polymerization, were characterized and purified prior to cellulose attachment. Oxidation of the cellulose microcrystal led to the formation of carboxylic acids on the surface of the microcrystals. Covalent attachment of the polymers onto the cellulose microcrystals was achieved via a carbodiimide-mediated amidation reaction. The length and diameter of the polymer-cellulose composites increased upon surface modification. Typically, polymer-cellulose composites are synthesized by a grafting-from method because it can be difficult to obtain sufficient graft density using a grafting-to preparation. However, the composites reported here comprised 60-64% grafted polymer by mass. This degree of grafting-to allowed the composite to form stable suspensions in organic solvents.